2009
DOI: 10.1007/s12079-009-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

The matricellular functions of small leucine-rich proteoglycans (SLRPs)

Abstract: The small leucine-rich proteoglycans (SLRPs) are biologically active components of the extracellular matrix (ECM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
171
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(174 citation statements)
references
References 150 publications
(266 reference statements)
1
171
0
2
Order By: Relevance
“…Thus, we hypothesized that aberrant expression of proteoglycans is a more frequent event and plays many physiological and pathological roles in the development and progression of tumors and merits further investigation. It is clear that SLRPs are biologically active components of ECM (26). ASPN, a new member of the SLRPs, is expressed abundantly in several malignant tumors, suggesting its involvement in the tumorigenesis and progression of cancer (6).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesized that aberrant expression of proteoglycans is a more frequent event and plays many physiological and pathological roles in the development and progression of tumors and merits further investigation. It is clear that SLRPs are biologically active components of ECM (26). ASPN, a new member of the SLRPs, is expressed abundantly in several malignant tumors, suggesting its involvement in the tumorigenesis and progression of cancer (6).…”
Section: Discussionmentioning
confidence: 99%
“…The role of Bgn in regulating cellular proliferation was addressed only in a limited number of studies (36). Recent studies using cDNA and proteomic technologies demonstrated a down-regulated mRNA expression of Bgn and decorin in osteosarcoma, leukemia, intrahepatic cholangiocarcinoma, and melanoma (21)(22)(23)37).…”
Section: Discussionmentioning
confidence: 99%
“…117 However, they are now recognized as key signaling molecules, mediating cell-matrix crosstalk and regulating cell behavior, suggesting their biological activity extends far beyond the ability to bind collagens. 118,119 Several SLRPs show altered expression levels during pressure overload-induced remodeling, 120, 121 but there is limited knowledge about their roles in the failing heart.…”
Section: Small Leucine-rich Proteoglycansmentioning
confidence: 99%